NATIONAL DENTAL HEALTH MONTH PROGRAM 2022 SCHOOL HEALTH PROGRAM WITH ITS KINDERGARTEN - Revianti, Syamsulina; Brahmanta, Arya; Agnita Cevanti, Twi; Puspita, Sinta; Khoironi, Emy; Pangabdian, Fani; Widaningsih, Widaningsih; Hanum, Faizah; Listya Paramita, Annisa; Dwi Maharani, Aulia; Paramita, Ayulistya; Iman, Dimas; Rizal, Mohammad Basroni; Anindya Pinasti, Restika; Soesilo, Diana (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Dental and oral health in Indonesia is still a health problem that needs attention. The most concerning thing is that as many as 93% of school-age children experience dental and mouth problems. This can be caused by a lack of knowledge and awareness of dental hygiene. One of the efforts made to increase knowledge and awareness of dental hygiene is by holding an educational activity called the "School Health Program". This activity was carried out in several schools, one of which was TK ITS. This activity began with the Training of Trainer Program given by dentists to teacher cadres and parents of students/students/students about the benefits of good oral hygiene and how to brush your teeth twice a day with fluoride toothpaste. Dentists provide educational materials using power point media and educational videos through the zoom application. There were 5 cadres consisting of 2 teachers and 3 guardians of students who attended this activity. After that, the teacher cadres and parents of the students/students disseminate information to other parents of students/students so that they can become mentors to their children to apply good and correct behavior of brushing their teeth twice a day for 21 days with the method recorded on the given calendar. The hope is that after this program ends, students at ITS Kindergarten have the behavior of maintaining oral hygiene by brushing their teeth twice a day with fluoride toothpaste.